Identity orientation affects rugby players` performance and decision making - Hacques, G.; Bourgeais, Q.; Campo, M.; Seifert, L. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction Recent work has shown that players in team sports can identify with their team or their personal identity, which influences their emotions and performance (Campo et al., 2018, 2019). The aim of this study is to examine the impact of self-oriented and group-oriented identities on rugby players` performance with a particular focus on individual players` decision making. We expected that identity processes would influence players` perceptions and actions, and that this effect would increase when players perform in complex situations (i.e., situations with many action possibilities).